ANALISIS KELONGSORAN PENGEMBANGAN RUAS JALAN BUJANGGA PINGGIRAN SUNGAI SEGAH KOTA TANJUNG REDEP KABUPATEN BERAU - Bagus Eko Prasetyo; Mansyur Mansyur; Fahrudi Ahwan Ikhsan; Andri Estining Sejati (Tunas Geografi, 2020)
This research discussed the effect of scouring on the stability of the slope on the Bujangga street STA 00+000 sd STA 00+075. A landslide had occurred in the development of a road located on the Bujangga riverside. The road is the result of widening which was previously only 2 lanes with a width of 8 m to 4 lanes with a width of 20 m. Landslides occured at STA 00+000 up to STA 00+075. At the STA the road experiences a landslide in the direction of the river to the elevation of the road surface down as deep as ± 2m. This research type is survey. Data was collected with documentation of post-landslide soil investigations, investigation of landslide conditions in the field, and sheet-pile slip simulation using the finite element method with helping the PLAXIS V.7.2 program. Data analysis with descriptive and back analysis to input soil parameters produces deformation and landslide mechanism that is relevant to actual conditions in the field. As a result of scouring of the river there is a reduction in passive pressure on the outside of the sheetpile which results in a decrease in the value of the safety factor of the road including other buildings such as settlements. This is indicated by the results of modeling and simulation above which gives the value of FS=1.2602 without scouring and FS=1.045 after scouring. The scouring of the river can be concluded that on a long-term scale the location is a landslide prone location.Keywords: Landslide Analysis, Finite Element, Road Development, Riverside  Penelitian ini membahas pengaruh scouring terhadap stabilitas lereng pada kelongsoran Jalan Bujangga STA 00+000 sd STA 00+075. Pernah terjadi kelongsoran pada pengembangan jalan yang berlokasi di pinggiran sungai Bujangga. Jalan tersebut merupakan hasil pelebaran yang sebelumnya hanya 2 lajur dengan lebar 8 m menjadi 4 lajur dengan lebar 20 m. Kelongsoran terjadi pada STA 00+000 sampai dengan STA 00+075. Pada STA tersebut jalan mengalami kelongsoran ke arah sungai hingga elevasi permukaan jalan turun sedalam ± 2m. Penelitian ini berjenis survey. Data dikumpulkan dengan dokumentasi penyelidikan tanah pasca longsoran, investigasi kondisi longsoran di lapangan, dan simulasi kelongsoran sheetpile menggunakan metode elemen hingga dengan bantuan program PLAXIS V.7.2. Analisis data dengan deskriptif dan back analysis hingga parameter tanah input menghasilkan deformasi dan mekanisme kelongsoran yang relevan dengan kondisi actual di lapangan. Akibat dari scouring atau gerusan sungai terjadi pengurangan tekanan pasif pada sisi luar sheetpile yang berakibat penurunan nilai faktor keamanan dari jalan termasuk bangunan lain seperti pemukiman. Hal tersebut ditunjukkan oleh hasil pemodelan dan simulasi di atas yang memberikan nilai FS=1.2602 tanpa scouring dan FS=1.045 setelah adanya scouring. Adanya gerusan pada bibir sungai dapat disimpulkan bahwa dalam skala jangka panjang lokasi tersebut merupakan lokasi rawan bencana longsoran.Kata Kunci: Analisis Longsoran, Elemen Hingga, Pengembangan Jalan, Pinggiran Sungai